PENGARUH PROMOSI ONLINE DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI KONSUMEN PADA AKUN INSTAGRAM “@CRSL.STORE” - Putri, Arnetta; Hatta, Iha Haryani; Savitri, Laili Noor (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
The field of the fashion industry continues to develop over time, marketing through social media is a major influence on consumer interest in shopping online. This study aims to determine and analyze the influence of online promotion and brand image on purchasing decisions through consumer buying interest on the Crsl store Instagram account. This research is a quantitative research with the type of explanatory research (explanatory Research). The sampling technique in this study uses the Probablility Sampling. The sample used was 129 respondents. The results of this study show that online promotion has a positive and significant effect on consumer buying interest and purchase decisions, brand image has a positive and significant effect on consumer buying interest and purchase decisions, consumer buying interest has a positive and significant effect on purchasing decisions, online promotion has a negative and insignificant effect on purchasing decisions through consumer buying interest and brand image has a positive and significant effect towards purchasing decisions through consumer buying interest in the Crsl Store. Key words: Online Promotion, Brand Image, Purchase Decision, Consumer Purchase Interest